'Consubstantiality' as a philosophical-theological problem: Victorinus' hylomorphic model of God and his 'correction' by Augustine. Issue 1 (February 2022) - Byers, Sarah
Abstract: This article expands our knowledge of the historical-philosophical process by which the dominant metaphysical account of the Christian God became ascendant. It demonstrates that Marius Victorinus proposed a peculiar model of 'consubstantiality' that utilised a notion of 'existence' indebted to the Aristotelian concept of 'prime matter'. Victorinus employed this to argue that God is a unity composed of Father and Son. The article critically evaluates this model. It then argues that Augustine noticed one of the model's philosophical liabilities but did not publicly name Victorinus when he rejected it, thereby exemplifying the New Testament practice of private 'rebuke' (ἐλέγχɛιν).